THE CONSTELLATION OF ACCOUNTANCY AND ECONOMICS. - Mattessich, Richard (The Accounting Review, 1956)
Abstract Accountancy and economics have the same objectives of cognition. Both branches examine the individual economic cell as well as the entire economic body of a country. In the center of these studies are the administration of scarce resources and the determination of income and production volume. It is often emphasized that the economist assumes the national, community or social point of view while the accountant is limited to the individual enterprise. But actually both branches have sections which deal with the national economy, that is, with the economic organism as an entity, or with the link between two or more national economies and both have sections dealing with firms, that is, with the ultimate bricks of this more highly organized structure. Business accounting can be regarded as that part of accountancy which is engaged in the studies of the firm, and microeconomics is its counterpart in economic analysis, while national accounting on one side, and macro-economics on the other, are dealing with the over-all picture of the economy.